RELEVANSI TEORI BRUNER DAN TEORI DIENES DALAM KEGIATAN PEMBELAJARAN MATEMATIKA KELAS II DI MADRASAH IBTIDAIYAH AL-MADINA KOTESAN, PRAMBANAN - Andi Setiyawan; Effendi Yulianto; M. Rofi Fauzi (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
Mathematics is one of the subjects taught in elementary schools which has its own level of difficulty in teaching. The selection of the right learning theory in teaching mathematics to children, especially when children are in elementary school education, will determine the level of success in learning. Bruner and Dienes learning theory is a cognitive learning theory where the learning process is based on the cognitive development of children and the learning process is student-centered. The purposes of this writing include; (1) to find out the application of Bruner and Dienes Theory in the second grade mathematics learning process at Madrasah Ibtidaiyah Al-Madina, (2) to describe the obstacles and solutions to the application of Bruner and Dienes Theory in the learning process both offline and online. The data collection technique used in this paper is a qualitative approach using the method of observation, documentation and interviews with second grade mathematics teachers at Madrasah Ibtidaiyah Al- Madina and also literature study.